Pengaruh Model Realistic Mathematics Education Berbantuan Metode Stemmatics terhadap Pemahaman Konsep Operasi Perkalian di Sekolah Dasar - Dina Nuryani; Isrok'atun Isrok'atun; Maulana Maulana (Universitas Negeri Padang, 2024)
The RME model combined with the stemmatics method is a solution to students' low ability to understand concepts in multiplication. The research method used is an experiment with a quasi-experimental design. The population chosen was elementary schools in North Sumedang District which were randomly selected with 30 students for control an experimental classes. The research location is North Sumedang District, Sumedang Regency. The research instrument is a test in the form of pretest-posttest questions. The data analysis techniques used are validity test, homogeneity test, normality test, hypothesis test, mean difference test (Wilcoxon dan Mann Whitney test), and N-Gain test. The N-Gain test shows that learning in the experimental class has a positive influence as evidenced by an increase in learning outcome of 0.64. Apart from that, learning in the experimental class was better, as evidenced by the control and experimental classes, namely 64.07 and 84.03. This proves that learning in the experimental class where RME learning was applied using the stemmatics method was better than learning in the control class where conventional learning was applied. This increase is also influenced by the use of candy cane media with colorful appearance which can increase students' attention and enthusiasm when learning takes place.